Preparing early childhood teachers for real-time and postdisaster classrooms: invisible capes and specialized planning - Cooper, Patricia M. (Journal of early childhood teacher education, 2019)
This essay addresses two types of disasters that can affect early childhood classrooms, which deserve more attention during teacher preparation. The first includes such natural phenomena as earthquakes and hurricanes, as well man-made events, such as fires and, incredibly, school shootings. They are almost always unexpected and happen in real time. Without question, they requires teachers' immediate, direct, and complete commitment. The second type is a disaster that has passed, but requires a focused and specialized curriculum when children return to school. The critically important role of early childhood teachers as "first responders" or "helpers" during and after disaster is discussed, along with best practices related to a "pedagogy of meaning" during these times.